The factors effecting entrepreneurial intention of university students: case of Mongolia - Zanabazar, Altanchimeg; Jigjiddorj, Sarantuya (The journal of contemporary issues in business and government, 2021)
Small and medium sized businesses with entrepreneur orientation have been developing rapidly in recent years creating the wealth for the nations and some of them often to lead becoming large global enterprises. As the phenomenon is progressing promptly, the interest in studying entrepreneur intention and the factors affecting to becoming entrepreneur in relation to the education and attitude. Numerous researches have been paid attention on investigating if the college program nurturing the intention of choosing entrepreneur or other factors contribute to boosting them to start own businesses among the college students as well as graduates. To contribute to the current field of the study, this study aims at researching different factors affecting the entrepreneur intention including some factors like attitude of the students, subjective norms, entrepreneur education and perceived behavior control using sample survey. The survey involved 568 business major college students. The results demonstrated that the personal attitude has a significant influence on entrepreneur intention as majority of participants expressed their willingness starting their own businesses despite potential challenges and opportunities they may face pursuing this career path. The determinants such as subjective norms and perceived behavior control both represented positive impacts on entrepreneurial intention of participants. Conversely, an entrepreneur education background or specifically the courses they completed so far on business related studies, in their view, had a slight impact in their entrepreneur intention.